2022
DOI: 10.1093/eurpub/ckac076
|View full text |Cite
|
Sign up to set email alerts
|

Using systems science methods to enhance the work of national and local walking partnerships: practical insights from Ireland

Abstract: Background Physical activity (PA) literature is dominated by individual-level descriptive studies, which are known to have limited impact on population PA levels. Leveraging systems science methods offers opportunities to approach PA in a manner which embraces its inherent complexity. This study describes how participatory systems mapping and social network analysis (SNA) were used to understand the work of local and national level walking systems in Ireland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Actions to leverage change included raising awareness with partners beyond the system, sharing policies, resources, insight, evidence, and capacity, and collaborating to co-produce a collective vision and strategy. These ndings complement and extend the growing body of evidence, which has utilised a pluralism of methodologies to understand the dynamic system underpinning participation in PA (19)(20)(21) and chart leverage points for change within this complexity (22,39,42,(46)(47)(48). This research provides important insight into the steps underpinning a shift towards a whole-systems and place-based approach to working.…”
Section: Discussionsupporting
confidence: 62%
“…Actions to leverage change included raising awareness with partners beyond the system, sharing policies, resources, insight, evidence, and capacity, and collaborating to co-produce a collective vision and strategy. These ndings complement and extend the growing body of evidence, which has utilised a pluralism of methodologies to understand the dynamic system underpinning participation in PA (19)(20)(21) and chart leverage points for change within this complexity (22,39,42,(46)(47)(48). This research provides important insight into the steps underpinning a shift towards a whole-systems and place-based approach to working.…”
Section: Discussionsupporting
confidence: 62%
“…Figure 2 exemplifies how centralities might be calculated on a fragment of the NCIPC model. These centrality measures have been used in numerous other studies on network science for public health (Power et al, 2022;Brauer et al, 2022;Smith et al, 2022), as well as in other comparative studies on systems maps (Krabbe, 2014;Kim and McCarthy, 2021;Wang and Giabbanelli, 2023).…”
Section: Analyzing Systems Mapsmentioning
confidence: 99%
“…Walking promotion and development is not the sole responsibility of one sector, organisation, or discipline. Previous work by our research group (11) has demonstrated the potential for systems science methods, specifically systems mapping, to assist with engaging multidisciplinary stakeholders at local level in Ireland. Although Power and colleagues used systems mapping as a catalyst to engage stakeholders, systems mapping can also (40), and acknowledging walking as its own transport mode when collecting data and devising policies is recommended (41), it must be noted that this approach to local level walking policies may exacerbate disciplinary siloes.…”
Section: Irish Walking Policy-synergies and Specificitiesmentioning
confidence: 99%
“…Engaging with multiple sectors has been noted as best practice in the PA policy development literature (20,21,42). However, a study conducted by Power et al (11) which used social network analysis methods to evaluate the communication network between the multidisciplinary actors involved in the implementation of the GIW SAP, found that there was a mismatch between how actors were required to communicate (based on collaborative actions in the GIW SAP) compared with how actors communicated in practice. The lack of clarity in relation to the roles and responsibilities of the stakeholders involved in the implementation of the GIW SAP may be explained by the lack of political leverage held by GIW.…”
Section: Irish Walking Policy-synergies and Specificitiesmentioning
confidence: 99%
See 1 more Smart Citation